An exploratory study of the role that identity documents play in the integration of refugees and asylum seekers in South Africa: reflections from Cape Town - Wamundiya, Alice (Department of Social Development, 2015)
South Africa is one of the top regional destinations for refugees and asylum seekers. The South African government has chosen to adopt local integration as its main strategy in dealing with the refugees and asylum seekers it currently hosts, as opposed to housing refugees in camps. This step has been hailed as progressive, and the Refugee Act has espoused the issuing of progressive identity documents to refugees and asylum seekers as the viaduct through which refugees and asylum seekers can become fully integrated. In this regard then, refugee and asylum seeker identity documents are critical and the study sought to investigate the extent to which this policy intent of using identity documents to facilitate integration had become a reality. The study began by looking at the evolution of refugee and asylum seeker law in South Africa. From there it looked at the differences between refugees and asylum seekers, and what distinguishes them from other migrants such as economic migrants. Thereafter the study looked at theoretical frameworks surrounding migration and integration, especially as pertains to the refugee and asylum seeker context. In particular, the study sought to present the experiences of identity documents in facilitating integration from two main perspectives namely the refugees and asylum seekers who are issued with and make use of these identity documents, and service providers who interact with these documents on a daily basis and provide services to the refugee and asylum seeker communities. The findings presented highlight that despite the progressive evolution of refugee law in South Africa, the role of these identity documents, in facilitating access to services and promoting integration, has largely failed, from the practical to the policy level.